Rapid glucocorticoid tapering therapy to reduce mortality from pneumocystis pneumonia in patients with rheumatic disease. Issue 4 (4th July 2019) - Ando, Taiki; Abe, Yoshiyuki; Endo, Yukari; Tada, Kurisu; Yamaji, Ken; Tamura, Naoto
Abstract: Objective: Pneumocystis pneumonia (PCP) is a serious complication in patients with rheumatic diseases who are receiving immunosuppressive therapy. These patients have a higher mortality from PCP than those with human immunodeficiency virus. We examined factors associated with poor prognosis in patients with rheumatic diseases and evaluated PCP treatment in this population. Methods: This retrospective, single-center, observational cohort study included 31 patients with rheumatic diseases who were admitted to Juntendo University Hospital for PCP treatment from June 2006 to December 2017. The primary outcome was non–disease-specific mortality at discharge. Results: The median age at PCP diagnosis was 64 years. The survival rate was 61.3% (19/31). Twelve patients died, in all cases due to respiratory failure due to PCP. Among variables at PCP diagnosis and those related to PCP treatment, the presence of coexisting pulmonary diseases and greater glucocorticoid dose at PCP diagnosis were associated with higher mortality. The mortality related to biological agents for PCP was low. Rapid tapering of glucocorticoids improved survivability. Conclusion: In the treatment of PCP in patients with rheumatic diseases, rapid tapering of glucocorticoids was associated with a higher survival rate than the use of conventional therapy.